HEALTH CARE–ASSOCIATED INFECTIONS AND THE RADIOLOGY DEPARTMENT - Hadeel Abdulrahman Hashim, Ahmed Saud Aldalbahi, Mohammed Sulaiman Abdulkarim (Chelonian Research Foundation, 2024)
This essay explores the issue of Health Care–Associated Infections (HAIs) in the context of the radiology department. The essay discusses the importance of addressing HAIs in the radiology department and presents a literature review on the topic. The methodology used for this essay includes a review of relevant research articles, guidelines, and reports. The results highlight the prevalence of HAIs in the radiology department and identify key risk factors. The discussion section explores strategies for reducing the risk of HAIs in the radiology department, including infection control measures and quality improvement initiatives. The conclusion emphasizes the need for a multidisciplinary approach to addressing HAIs in the radiology department and underscores the importance of patient safety in healthcare settings.